Is there a Jewish philosophy? : rethinking fundamentals - Roth, Leon, 1896-1963 (Littman library of Jewish civilization (Series), 1999)
Elegantly written essays provide an engaging, thought-provoking discussion of the fundamentals of Judaism, in which the application of Jewish ethical principles shines through.